The Effect of Product Innovation on Repurchase Intentions Mediated by Consumer Satisfaction of Oppo Smartphone Users - Elsa H.M Manuhutu; Arasy Alimudin; Ani Wulandari; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the effect of product innovation on repurchase intentions mediated by consumer satisfaction on Oppo smartphone users at NAROTAMA University, UBAYA and UKWMS. This study was conducted in the city of Surabaya using path analysis data analysis techniques. The sample size obtained by using the purposive sampling method was 99 respondents. Based on the results of the analysis, it was found that product innovation has a positive and significant effect on consumer satisfaction for Oppo smartphones. Product innovation has a positive and significant effect on the repurchase intention of Oppo smartphone consumers. Consumer satisfaction has a positive and significant effect on the repurchase intention of Oppo smartphone consumers. Consumer satisfaction mediates the positive effect of product innovation on the repurchase intention of Oppo smartphone consumers. The advice recommended by the Oppo smartphone company is to provide the latest innovations for Oppo smartphone products so that users can comfortably use their products and an evaluation is held for each of the latest products or variants, to be able to see the user's needs.